MODERASI BERAGAMA DALAM PENDIDIKAN ISLAM - Mustofa, Alik; Putri Yudhiarti, Ndaru (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2024)
Education in Indonesia faces challenges in integrating the values of religious moderation, especially in the context of social and cultural diversity. This article explores how religious moderation can be implemented in Islamic education curricula to promote tolerance, understanding, and inclusive attitudes among students. Using a qualitative approach, this study analyzes successful educational practices and the barriers that exist in teaching religious moderation. The research results show that the application of religious moderation in Islamic education not only strengthens religious values but also supports the formation of students’ characters who are adaptive to differences. These findings provide recommendations for policy makers and educators to develop more effective strategies in teaching religious moderation as an integral part of Islamic education